2012
DOI: 10.1080/02699931.2011.574873
|View full text |Cite
|
Sign up to set email alerts
|

Affective state and event-based prospective memory

Abstract: Event-based prospective memory tasks require the realisation of a delayed intention at the occurrence of a specific target event. The present research investigates how performance in this kind of prospective memory task is influenced by the current affective state. By manipulating participants' mood during intention realisation we tested two competing models of mood effects on memory (i.e., a capacity consuming account and a processing style account). Furthermore, we manipulated the valence of the target event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 33 publications
2
35
3
Order By: Relevance
“…Results from mediation analyses showed that positive, as well as negative, mood reduced time monitoring which then led to the impairment in PM performance. This finding helps to clarify the conflicting results from the two former studies on mood effects in PM in the young (Kliegel et al, 2005;Rummel et al, 2012). As these studies used different PM tasks which differently require controlled attention (event-based, where the prospective response is triggered by an external cue that needs to be identified as such vs. time-based, where proactive and strategic deployment of controlled attention across the entire task is a constitutive requirement for not missing the target times), performance may be influenced by mood in different ways (i.e.. via cue identification vs. proactive and strategic time monitoring).…”
Section: Discussionmentioning
confidence: 62%
“…Results from mediation analyses showed that positive, as well as negative, mood reduced time monitoring which then led to the impairment in PM performance. This finding helps to clarify the conflicting results from the two former studies on mood effects in PM in the young (Kliegel et al, 2005;Rummel et al, 2012). As these studies used different PM tasks which differently require controlled attention (event-based, where the prospective response is triggered by an external cue that needs to be identified as such vs. time-based, where proactive and strategic deployment of controlled attention across the entire task is a constitutive requirement for not missing the target times), performance may be influenced by mood in different ways (i.e.. via cue identification vs. proactive and strategic time monitoring).…”
Section: Discussionmentioning
confidence: 62%
“…We emphasize that our manipulation of emotion was specific to PM cues, and not to the emotional state of the participants. Indeed, a very different pattern might emerge when the emotional state of participants is varied, as people in a happy mood tend to show diminished PM success, while those in a sad mood tend to show elevated PM success (Rummel, Hepp, Klein, & Silberleitner, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Kliegel et al (2005) found that performance on a time-based prospective memory task (i.e., remembering to do something at a certain time) was impaired under sad mood compared to neutral mood. However, Rummel, Hepp, Klein and Silberleitner (2012) observed that participants showed better performance in an event-based prospective memory task (i.e., remembering to do something after the recognition of an external cue in the environment) under sad mood. Yet, prospective memory was found to be impaired under positive mood.…”
Section: Mood Effects On Memory and Executive Control In A Real-life mentioning
confidence: 99%
“…This was the case in the task measuring cognitive flexibility in the present study (i.e., generating new words). For prospective memory, Rummel et al (2012) only found impaired execution of delayed intentions under positive compared to negative mood, but not compared to neutral mood. Thus, this effect was partly caused by improved performance under negative mood and might explain why we did not find mood effects on prospective remembering in the current study as we only compared neutral and positive mood effects.…”
Section: Mood and Cognition In Everyday Life 13mentioning
confidence: 99%